PERAN PEJABAT GEREJA BETHEL INDONESIA DALAM PENGUATAN MODERASI BERAGAMA DI KOTA BATAM - George Rudi Hartono Pasaribu (JURNAL TABGHA, 2023)
Indonesia, consisting of various ethnicities, customs, races, and beliefs, is a richness not possessed by other nations, but on the other hand, it can be a threat to division if these differences are not nurtured with good understanding, especially in the understanding of religious moderation. The values of tolerance among different religious communities can be developed through a moderate religious understanding. The officials of the Bethel Church Indonesia, as part of the Indonesian society and also as a church with a national orientation, play a crucial role in providing education to the congregation and the community, and can also serve as a driving force in strengthening religious moderation. Therefore, a foundation and understanding of how GBI officials can actively, inclusively, and practically contribute to achieving this goal are needed. This research employs a method known as descriptive research with a qualitative approach, where the phenomena or objects under study are clearly obtained. Therefore, in the overall process, data analysis techniques are utilized to explore various sources of information such as books, online and offline journals, both national and international, articles, and other bibliographic sources. In practice, it can be seen through the awareness and acceptance of ethnic or racial differences by preaching or teaching the congregation about the importance of understanding religious moderation, preserving and applying the noble values of the Indonesian nation, namely "Bhineka Tunggal Ika". Furthermore, providing an understanding to all officials that differences are a national wealth, developing inclusivism as an Indonesian cultural value through tangible actions like engaging in joint discussions, and conducting social activities together among communities and between churches and the community.